2008
DOI: 10.1088/0029-5515/48/2/024004
|View full text |Cite
|
Sign up to set email alerts
|

Study of in-vessel nonaxisymmetric ELM suppression coil concepts for ITER

Abstract: Large Type-I edge-localized mode (ELM) heat pulses may limit the life of divertor targets in a burning plasma. Recent experiments show that pitch-resonant nonaxisymmetric magnetic perturbations of the plasma edge of 0.0005 or less of the main magnetic field offer a useful solution, but there is little room in the presently designed ITER for even small perturbation coils. We present proposed coil requirements for ITER ELM suppression, derived primarily from DIII-D ELM suppression experiments. We show by calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(169 citation statements)
references
References 31 publications
4
164
0
1
Order By: Relevance
“…Instead, the flux surface averaged current density used in the equilibrium calculations was set to the sum of the neoclassical bootstrap current, given by the Sauter expression, 8 and the fully relaxed Ohmic current using neoclassical resistivity. Finally, a complete RMP mode spectrum analysis using the SURFMN code, 53 including calculation of the Chirikov parameter profile in the edge, was done on each kinetic EFIT including the I-coil n = 3 perturbation, the n = 1 perturbation from the C-coil, and the measured n =1, 2, and 3 error fields. 63 This calculation used only the vacuum fields without any correction for the plasma response, so any effects of screening or amplification of the perturbation fields due to the plasma response are not included here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the flux surface averaged current density used in the equilibrium calculations was set to the sum of the neoclassical bootstrap current, given by the Sauter expression, 8 and the fully relaxed Ohmic current using neoclassical resistivity. Finally, a complete RMP mode spectrum analysis using the SURFMN code, 53 including calculation of the Chirikov parameter profile in the edge, was done on each kinetic EFIT including the I-coil n = 3 perturbation, the n = 1 perturbation from the C-coil, and the measured n =1, 2, and 3 error fields. 63 This calculation used only the vacuum fields without any correction for the plasma response, so any effects of screening or amplification of the perturbation fields due to the plasma response are not included here.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work surveyed a range of possible RMP coil designs for ELM control in ITER. 53 In this kind of survey the first specification that must be made is the current required in the coils to satisfy a criterion for ELM suppression. From the results reported here, an initial estimate of the required coil currents for the different candidate designs was made based on a criterion that the coils must produce a Chirikov parameter greater than 1.0 from the plasma edge to ⌿ N = 0.85.…”
Section: Discussion Of Theory: Experiments Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently it has been found that RMPs produced by special coils can be very effective in mitigation and even complete suppression of edge-localized modes. [1][2][3][4] Numerous theoretical studies have been performed in order to describe those experiments and specific features of particle and energy transport in the presence of RMPs. [5][6][7][8][9][10][11][12][13][14] Diverse mechanisms of the RMP effect on transport processes revealed in these studies rely significantly on the level of the perturbation amplitude in the edge plasma.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was discovered on DIII-D [11], and experimentation continues on DIII-D, ASDEX Upgrade and several other tokamaks. Because of the importance of controlling ELMs, a set of RMP coils has been designed for ITER [12], based on empirical criteria developed on DIII-D. According to these criteria, the magnetic perturbation spectrum, characterized by poloidal mode number m and toroidal mode number n should have a peak near the resonance with the pitch of the magnetic field lines at the plasma edge, i.e.…”
Section: Resonant Magnetic Perturbation Coilsmentioning
confidence: 99%